Medical Emergency Response Plan: Case Study in a Mining Company - Dony Septriana Rosady (UNISBA Press, 2024)
Abstract. Medical emergency condition can occur unexpected and caused by human factors or unsafe actions. Mining companies need to have a system for handling medical emergencies that can be caused by physical, chemical, biological or other forms of danger. Lack of medical emergency response plan led to delay in evacuation and risking more lives to the hazards and harmed.The research uses a qualitative research design with a case study approach. The research was conducted at PRN Mining Company. Data collection was carried out using observation techniques, interviews and documentation studies of company regulations. Data collection and analysis was carried out using a focus group discussion method involving 9 people with proportional representation from HSE management elements, company doctors and practitioners in the field of occupational medicine. The research was conducted in the period January – April 2023. A medical emergency response plan is a set of written procedures that guide emergency actions, facilitate recovery efforts, and reduce the impact of emergency events. In mass medical emergencies, triage is an effort to sort and determine priorities for medical emergency response actions based on treatment needs and availability of resources. This mining company use the Simple Triage And Rapid Treatment (START) method for triage system. The work environment must be maintained in a safe condition for workers by implementing hierarchical control. The company needs to prepare policies and standard operational procedures for handling medical emergencies and prevent worsening of medical emergencies. The medical emergency response plan requires regular monitoring and evaluation to make adjustments based on company needs and scientific developments. Abstrak. Kondisi darurat medis dapat terjadi secara tidak terduga dan disebabkan oleh faktor manusia atau tindakan yang tidak aman. Perusahaan pertambangan perlu memiliki sistem penanganan darurat medis yang dapat disebabkan oleh bahaya fisik, kimia, biologi atau bentuk bahaya lainnya. Kurangnya rencana tanggap darurat medis menyebabkan tertundanya evakuasi dan mempertaruhkan lebih banyak nyawa dalam bahaya dan korban jiwa. Penelitian ini menggunakan desain penelitian kualitatif dengan pendekatan studi kasus. Penelitian ini dilakukan pada Perusahaan Pertambangan PRN. Pengumpulan data dilakukan dengan teknik observasi, wawancara dan studi dokumentasi terhadap peraturan perusahaan. Pengumpulan dan analisis data dilakukan dengan metode diskusi kelompok terfokus yang melibatkan 9 orang dengan keterwakilan proporsional dari unsur manajemen HSE, dokter perusahaan dan praktisi di bidang kedokteran kerja. Penelitian dilakukan pada periode Januari – April 2023. Rencana tanggap darurat medis adalah serangkaian prosedur tertulis yang memandu tindakan darurat, memfasilitasi upaya pemulihan, dan mengurangi dampak kejadian darurat. Dalam kedaruratan medis massal, triage merupakan upaya memilah dan menentukan prioritas tindakan tanggap darurat medis berdasarkan kebutuhan pengobatan dan ketersediaan sumber daya. Perusahaan pertambangan ini menggunakan metode Simple Triage And Rapid Treatment (START) untuk sistem triage. Lingkungan kerja harus dijaga dalam kondisi aman bagi pekerja dengan menerapkan pengendalian hierarki. Perusahaan perlu menyiapkan kebijakan dan standar prosedur operasional untuk penanganan kedaruratan medis dan mencegah memburuknya kedaruratan medis. Rencana tanggap darurat medis memerlukan pemantauan dan evaluasi secara berkala untuk melakukan penyesuaian berdasarkan kebutuhan perusahaan dan perkembangan ilmu pengetahuan.